ANALISIS REDAMANTERHADAP PERFORMANCEDENSE WAVELENGTH DIVISION MULTIPLEXING (DWDM)PADA SISTEM KOMUNIKASI SERAT OPTIKDENGAN METODE LINK POWER BUDGET DI PT. TELKOM PADANG (STUDI KASUS LINK PADANG – LUBUK BASUNG) - Farta Wendy Herdianta; Hanesman Hanesman; Delsina Faiza (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The research was conducted by analyzing the optical fiber attenuation of the DWDM performance in terms of power received on optical fiber communication systems link Padang-Lubuk cone in PT. Telkom Padang. Optical fiber has a very small damping. Therefore optical fibers become the primary choice in telecommunications networks. To improve the transmission quality is better then the use of DWDM technology, DWDM technology is a method to insert a number of channels were transmitted in a single optical fiber. Instruments in this study is the Power Meter and OTDR JDSU MTS-2000 type, the type of cable used G.655 Single Mode type. Link Power Budget method is used to determine the performance of DWDM caused by attenuation based on the value of the received power output receiver. On the link Padang - Lubuk cone highest attenuation occurs in core 1 of 29.742dB with 100.035 km cable lengths, and the core 10 of 31.8 dB with 119.998 km cablelengths. Based on the large fault or attenuation/km core 1 of 0.297 dB/km, the core 10 of 0.265 dB/km and the standard ITU-T was 0.35 dB/km. Value attenuation/km core 1 and core 10 is still in normal conditions and under standard ITU-T 0.35 dB/km. Based on optical fiber attenuation, the results of analysis of the link power budget is the value of Rx is smaller than the value of Rx sensitivity of -27 dBm, it can be said performance DWDM optical fiber communication systems in normal and can be used to operate because the power output can still be accepted by receiver in the device. Keywords:optical fiber cable, optical fiber attenuation, DWDM, link power budget.